Characteristics of biological therapy in pediatric patients with Crohn's disease. (4th March 2019) - Tarnok, Andras; Kiss, Zoltan; Kadenczki, Orsolya; Veres, Gabor
ABSTRACT: Introduction : At present, there is a significant amount of data related to biologics used in pediatric patients with Crohn's disease. This review characterizes the different biological drugs administered in this population. Areas covered : Biological therapy of CD, focusing on children, is summarized in this review. After mechanism of action and pharmacokinetics are described, mucosal healing on anti-TNF therapy, aspects of early therapy, long-term outcome and combination therapy are discussed. Moreover, loss of response and treatment optimization, as well as drug withdrawal are summarized. Subsequently, perianal disease and surgical aspects are discussed followed by safety issues. In addition, new drugs (vedolizumab, ustekinumab), cost-effectiveness and administration of biosimilars were also included. Expert commentary : There are significant data to characterize biological drugs administered in pediatric patients with Crohn's disease. However, head-to-head comparative studies using different biologics are missing.